Analisis Peran Konsultan Pajak Annajah Kota Bengkulu dalam Optimalisasi Pengelolaan Pajak Perusahaan Berbasis Ekonomi Syariah - Resti Nurholifah; Ira Mayang Sari; Yuninda Een Fryanti (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2024)
This research aims to analyze the role of Annajah Tax Consultants in optimizing company tax management based on sharia economics in Bengkulu City. Tax consultants play a very important role in helping companies to fulfill their tax obligations in a legal manner and in accordance with sharia principles, such as avoiding the practices of riba, gharar (uncertainty), and maysir (gambling). Annajah Tax Consultants provide education and counseling to companies regarding the importance of complying with tax regulations and sharia economic principles. By optimizing sharia-based tax management, companies can increase cost efficiency, improve the company's image, and gain the trust of investors and the public. This research concludes that the role of a good tax consultant can have a positive impact on the efficiency of company tax management in Bengkulu City, which ultimately supports company growth and sustainability.